(untitled) (Dhaka University Journal of Biological Sciences, 2016)
The study was conducted to determine the impact of seasons, host size and sexes on the incidence of helminth community infecting Channa striatus (Bloch, 1793) from Punarbhaba and Atrai rivers of Dinajpur district. Four helminths were identified: one Cestoda, Bothriocephalus cuspidatus (Cooper, 1917); two Nematoda, Ascaridia spp. (Dujardin, 1845) and Camallanus intestinalus (Bashirullah, 1974); one Acanthocephala, Pallisentis ophiocephali (Thapar, 1930). Out of 75 hosts examined 52 were infected by 326 helminth parasites. Nematoda was the most dominant group (48.0%), followed by Acanthocephala (46.67%) and Cestoda (8.0%). The larger hosts were more infected than the smaller ones. A significant positive correlation was observed between the length of the host with respect to the abundance and prevalence of parasite for C. intentinalus and P. ophiocephali. Regarding the effect of seasonal changes, the prevalence of B. cuspidatus (14.81%) and Ascaridia spp. (22.22%) was highest in the rainy season. The highest prevalence of C. intestinalus (73.91%) was observed in winter. The prevalence of P. ophiocephali was high (84.0%) in summer. Except the abundance of B. cuspidatus (p = 0.147) all parasite species, Ascaridia spp. (p = 0.003), C. intestinalus (p < 0.01) and P. ophiocephali (p < 0.01) varied significantly among seasons. Overall prevalence of infection of male and female were 53.8% and 77.6%, respectively. A significant difference in the abundance of the parasite species with respect to host sex was observed only in C. intestinalus (Z = 2.886, p = 0.004). Dhaka Univ. J. Biol. Sci. 25(1): 39-46, 2016